Advanced MR imaging in neuro-oncology - Radbruch, Alexander; Bendszus, Martin (Clinical neuroradiology, 2015)
The value of magnetic resonance (MR) imaging for the clinical management of brain tumour patients has greatly increased in recent years through the introduction of functional MR sequences. Previously, MR imaging for brain tumours relied for the most part on contrast-enhanced T1-weighted MR sequences but today with the help of advanced functional MR sequences, the pathophysiological aspects of tumour growth can be directly visualised and investigated. This article will present the pathophysiological background of the MR sequences relevant to neuro-oncological imaging as well as potential clinical applications. Ultimately, we take a look at possible future developments for ultra-high-field MR imaging.
Gesehen am 16.07.2020